Digital Financial Literacy and Individual Financial Performance: An Analysis of Generation Z - Mayndarto, Eko Cahyo; Wulandari, Wulandari; Kalsum, Ummy (PT. Hafasy Dwi Nawasena, 2026)
This study examines the influence of digital financial literacy on individual financial performance among Generation Z in Indonesia amid the rapid development of digital financial technology that has transformed financial management practices. As digital natives, Generation Z possesses strong potential to utilize digital financial tools, yet the relationship between digital financial literacy and financial performance remains underexplored. Using a quantitative survey approach, data were collected from 131 respondents aged 18–27 years through structured questionnaires and analyzed using multiple linear regression. The findings indicate that digital financial knowledge, digital financial skills, and digital financial behavior all have a significant positive effect on individual financial performance. Digital financial knowledge emerged as the strongest predictor (β = 0.421, p < 0.001), followed by digital financial skills (β = 0.318, p = 0.003) and digital financial behavior (β = 0.263, p = 0.012). Furthermore, the model explains 61.7% of the variance in financial performance (R² = 0.617). These findings demonstrate that digital financial literacy is a crucial determinant of financial well-being among Generation Z and highlight the importance of strengthening digital financial education through both formal and informal learning environments in the digital era.